THE EFFECT OF PROMOTION, FINANCIAL CAPABILITY, AND EASE OF TECHNOLOGY ON DECISIONS TO USE E-WALLET (CASE STUDY: GOPAY USERS IN DKI JAKARTA) - Divia Priscilla; Harya Kuncara Wiralaga; Karunia Dianta Arfiando Sebayang (International Journal of Multidisciplinary Research and Literature, 2023)
This study aims to investigate the factors namely, promotion, financial capability, and ease of technology that influence people's choices regarding whether or not to use Gopay in DKI Jakarta. Methods based on quantitative analysis in this line of research. This study's data source is primary data. Purposive sampling is used to collect data, with criteria including Gopay users who live in DKI Jakarta, are between 18 and 30, and have used Gopay wallets at least twice. The research sample amounted to 100 respondents. This study uses the multiple linear Regression analysis method. The results of this study indicate that 1) Promotion has a positive and significant effect on the decision to use the Gopay in DKI Jakarta, 2) Financial capability has a positive and significant effect on the decision to use the Gopay in DKI Jakarta, 3) The ease of technology has a positive and significant effect on the decision to use the Gopay in DKI Jakarta, and 4) Promotion, financial capability, and ease of technology simultaneously have a significant effect on the decision to use the Gopay in DKI Jakarta